The minimum wage - Shields, B. F. (Statistical and Social Inquiry Society of Ireland, 1934)
There are many types of minima, which are the outcome of personal negotiations or collective bargaining between employers and employees, and in which training, general skill, special aptitude, intellectual ability, experience and other qualifications are taken into account in determining the personal or standard wage for particular individuals or classes in the community. It is advisable, in view of the varied meanings to be attached to a minimum wage, to confine our analysis to the minimum personal or family wage of the fulltime unskilled worker.
Read before the Society on Friday, 25th May, 1934
Keywords: Minimum wage; Cost of Living; 314.15